Memórias cartaginesas: modernismo, antiguidade clássica e a historiografia da Independência do Brasil na Amazônia, 1823-1923 - FIGUEIREDO, Aldrin Moura de (2013)
This article analyzes the historiographic debates held in 1923 during the celebrations of the joining of Pará State to the Independence of Brazil. To do so, it examines the uses by local intellectuals of political myths of Classic Antiquity, as the Punic Wars, and of a series of concepts transmitted internationally in the 1910's and 1920's in political and literary works, as Keynes' "Carthaginian peace" (1919), Elliot's "West Land" (1922) and Flaubert's images of Carthage (1862). More than an erudite exercise, this analytical repertoire expressed the long and difficult process of building a "modern" national identity in Brazilian Amazon.